PENERAPAN ECOPRINT SEBAGAI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) UNTUK MENGEMBANGKAN KREATIVITAS SISWA SEKOLAH DASAR - M. Guntur Firdaus; Nisa Alfiah; Nur Irmayati; Arselina Khaero Putri; Bunga Tenri Sanna; Baiq Yuni Wahyuningsih (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
This community service aims to describe the implementation of ecoprint activities in the Pancasila Student Profile Strengthening Project (P5) and its contribution to the development of creativity of fifth-grade students at SDN 15 Cakranegara. The initial problem found was the low creativity of students due to the lack of variety of handicraft activities that only focused on drawing, coloring, and copying patterns. This community service uses a project-based learning approach where students are given a project in the form of ecoprint preparation activities integrated into the Pancasila Student Profile Strengthening Project (P5). The main stages of this community service activity are: (1) introduction of the concept; (2) exploration of local leaves and flowers; (3) hammering process, & (4) to the finishing stage of the tote bag. This activity involved 35 fifth-grade students, class teachers, and P5 accompanying teachers. The results of the community service show that ecoprint activities are able to increase students' creativity through a series of stages of natural material exploration, leaf composition arrangement, hammering process, and work evaluation. Students demonstrated active involvement, courage to experiment, and the ability to produce original designs. The variety of tote bag motifs produced shows the development of divergent thinking skills and artistic expression. Furthermore, the ecoprint project also contributed to strengthening the Pancasila Student Profile, particularly in the dimensions of creativity, independence, mutual cooperation, and respect for nature. Exploration-based activities and group work encouraged students to collaborate, discuss, and appreciate the environment as a source of inspiration for their work. Thus, ecoprinting proved to be an effective, contextual, and relevant alternative craft activity for enhancing the creativity of elementary school students.